ANALISIS KEMAMPUAN KOMUNIKASI PEMBELAJARAN GURU SEKOLAH MENENGAH KEJURUAN (SMK) DAN SEKOLAH MENENGAH ATAS (SMA) BISNIS DAN MANAJEMEN DI KOTA PADANG - Rita Syofyan (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2018)
This study aims to analyze the communication skills of teacher learning. This research is descriptive associative research. The population of this research is High School (SMA) teacher and Vocational High School (SMK) teacher in Padang City. The sampling technique used Purposive Random Sampling and obtained total of 30 samples. Questionnaires are used to obtain data. The results of this study indicate that communication learning is very important in supporting the achievement of learning objectives. Therefore, it is suggested to High School and Vocational High School teachers in Padang City to improve the communication skills of learning both in verbal and non verbal form